An evaluation of the effectiveness of the roving reference service of the Southville International School college library - Javier, Ramil V. (2016)
Roving reference is a form of reference service where the librarian himself approaches the user for queries. In the Philippines, few studies are done in the effectiveness of roving reference service in academic libraries. An example would be De La Salle University's study of its own Roving information Assistant (RIA) for this study, te chosen institution in Southville International School College Library.